FUZZY RELIABILITY ANALYSIS OF CONTACT FATIGUE STRENGTH OF DOUBLE SHOCK SLEEVE MOVABLE TEETH TRANSMISSION BASED ON AN IMPROVED RSM - LIU Jun; AN ZiJun (Jixie qiangdu)
An improved RSM was proposed to improve the computational efficiency and accuracy of contact fatigue fuzzy reliability analysis of double shock sleeve movable teeth transmission.Based on fuzzy theory,an improved RSM model is established by combining intelligent algorithm and reliability analysis method.Based on the theory of stress-strength interference,the interference reliability model is established with moment,elastic modulus,Poisson’s ratio and working tooth length are taken as input random variables and contact strength of meshing pair is taken as input fuzzy variables.Fuzzy reliability is calculated by different methods,and the distribution characteristics and fuzzy reliability of each response result are obtained.The comparison shows that the improved RSM improves the speed and accuracy of the calculation.